Student Worksheets Microbial Concepts Based On Urban Wetlands to Improve Critical Thinking Skills at High School Levels - Muhammad Zaini; Sri Amintarti; Aulia Ajizah; Datin Maghfirotul Nadhira; Mirna Hariati; Hidayati Hidayati (Master Program of Biology Education, Universitas Lambung Mangkurat, 2020)
Implementation of the 2013 curriculum has generally used recommended models, but the role of the work-sheets used in the learning process still does not facilitate students' critical thinking skills. The research aims to evaluate the validity, practicality, and effectiveness of the development worksheets on the microbial concepts based on urban wetlands to improve students' critical thinking skills. The development of work-sheets was carried out in 2 phases; preliminary research phase and prototype phase using the Tessmer design. Content validation uses a validation assessment sheet instrument. The practicality data of the contents was using an assessment sheet instrument on the worksheet structure. Practicality data (expectations and actual) were collected using a practicality sheet instrument obtained from students' responses to the contents of the worksheet. Effectiveness data (expectations and actual) are obtained based on the results of critical thinking skills, interpersonal skills (cooperation), and intra-personal skills (responsible). Data analysis techniques by calculating the percentage of validation refer to Akbar (2017), practicality test, and effectiveness test with criteria referring to Purwanto (2012). The results showed that worksheets for students were valid and were practical for users with the practicality of contents and practicality of expectations is good. Work-sheets was declared to be effectively used based on the results of the critical thinking skills, interpersonal skills (collaboration), and intra-personal skills (meticulous), and the value of the effectiveness of expectations is good categories too.AbstrakImplementasi Kurikulum 2013 umumnya telah menggunakan model-model yang direkomendasikan, namun peran LKPD yang digunakan dalam proses pembelajaran masih belum memfasilitasi keterampilan berpikir kritis (KBK) peserta didik. Penelitian bertujuan mengevaluasi validitas, kepraktisan,dan keefektifan LKPD hasil pengembangan pada konsep-konsep dunia mikroba berbasis lahan basah perkotaan untuk meningkatkan keterampilan berpikir kritis peserta didik. Pengembangan LKPD dilakukan 2 fase; fase penelitian pendahuluan dan fase prototipe dengan menggunakan desain Tessmer. Validasi isi menggunakan instrumen lembar penilaian validasi. Data kepraktisan isi menggunakan instrumen lembar penilaian terhadap struktur LKPD. Data kepraktisan (harapan dan actual) dikumpulkan menggunakan instrumen lembar kepraktisan yang diperoleh dari respon peserta didik terhadap isi LKPD. Data keefektifan (harapan dan aktual) diperoleh berdasarkan hasil KBK, keterampilan inter-personal (kerjasama) dan keterampilan intra-personal (bertanggung jawab). Teknik analisis data dengan menghitung persentase validasi mengacu pada Akbar (2017), uji kepraktisan dan uji keefektifan dengan kriteria mengacu pada Purwanto (2012). Hasil penelitian menunjukkan bahwa LKPD valid, namun LKPD yang dikembangkan praktis digunakan dengan kepraktisan isi dan kepraktisan harapan yang berkategori baik. LKPD dinyatakan efektif digunakan berdasarkan hasil KBK, keterampilan inter-personal (kerjasama), dan keterampilan intra-personal (teliti) maupun nilai keefektifan harapan juga berkategori baik.